Editor's Note - Robyn Williams; Lisa Otto (The Thinker)
Emerging and advanced technologies continue to creep into public and private life. Particularly forceful, the fourth industrial revolution (4IR) is unavoidable. New and advancing technologies such as artificial intelligence, big data and the Internet of Things have injected themselves in big and small ways in various aspects of daily life. Lavopa and Delera (2021) note that 4IR is much more than a ‘technological leap forward’; indeed, this industrial revolution is likely to have much wider-reaching consequences than any other than has come before it.